The Effect of Audit, Corporate Culture, Audit Committee, Inspection, Policies and Procedures, and it Adoption on Fraud Effectiveness Risk Management Banking Industry in Indonesia - Jonathan Tanuwijaya; Chandra Restu Pradipto (Green Publisher Indonesia, 2023)
Fraud is a morally repugnant, illegal, costly societal issue. Because fraud has such a negative impact on economic development, profitability, and the welfare of business, it has emerged as a major threat on a global scale. Moreover, each year, there are a growing number of instances of fraud that are recorded. In Recent years, instances of fraud have captured the attention of the general public. This study aims to determine whether internal audit, corporate culture, audit committees, inspectors, policies, and procedures as well as the adoption of information technology affect the effectiveness of management fraud risk in the banking sector in Indonesia or not. The study uses quantitative research method. The results of study show that anternal audit, inspection, and IT adoption were discovered to have a positive and significant relationship with the efficiency of bank fraud risk management by the researchers. While other variables, such as corporate culture, audit committee, and policies and procedures, have a negative relationship with the effectiveness of fraud risk management, the policies and procedures have no significant impact on the effectiveness of fraud risk management.